The Effect of Organizational Culture on Employee Performance Mediated by Work Stress: Study at PT ADIRA Dinamika Multifinance in Denpasar - I Kadek Dwi Putra Yoga; Ni Wayan Sitiari; I Made Sara; Putu Pertamawati (Universitas Warmadewa, 2018)
Abstract-Performance is a real behavior that is displayed by every person as a work performance generated by employees in accordance with its role in the company. Employee performance is a very important thing in the company's efforts to achieve the company goals. Organizational culture is a habit that has lasted long, used and applied in the circulation of work activities as one of the drivers to improve the work quality of employees and managers of the company. Work stress is a condition of tension that creates a physical and psychological imbalance, affecting the emotions, thought processes, and conditions of an employee. Excessive stress can threaten a person's ability to cope with the environment. As a result, employees develop a variety of stress symptoms that can interfere with their work. This study aims to examine how the influence of organizational culture on employee performance is mediated by work stress. Participants in this study were 78 respondents who were employees of PT. Adira Dinamika Multi Finance in Denpasar. The method of determining the sample used was random sampling. Data collection was done through interview and questionnaire distribution. Data analysis was done by using descriptive analysis and inferential analysis. The research hypothesis was tested using Partial Least Square (PLS) application. The results showed that: (1) Organizational culture has a positive and significant effect on employee performance. (2) Organizational culture has a positive and significant impact on work stress. (3) Work stress has a positive and significant effect on employee performance. (4) Work stress is a perfect mediation between organizational cultures on the performance of employees of PT. Adira Dinamika Multi Finance in Denpasar. Keywords: Organizational Culture; Work Stress and Employee Performance.